A spoonful of sugar: the application of glycopolymers in therapeutics - Spain, Sebastian G.; Cameron, Neil R. (Royal Society of Chemistry, 2011)
Glycopolymers, synthetic polymers displaying carbohydrate moieties, have been linked to many potential applications at the biology–chemistry interface. One area that holds particular promise is the employment of glycopolymers as vehicles for therapeutics or as therapeutics themselves. This review summarises some of the more prominent examples as well as those in the early stages of development.